Optical Anomalies due to Volume Collective Modes of Plasmonic Metamaterials. Issue 4 (19th January 2023) - Ben‐Haim, Danielle; Ellenbogen, Tal
Abstract: The emergence of optical anomalies in 3D plasmonic metamaterials upon excitation of volume collective modes is studied. These modes engage a collective response of all the meta‐atoms across the volume of the structure and arise due to coupling of localized plasmonic modes with Bloch modes of the 3D lattice. Two types of volume collective modes are introduced; a reflective mode resilient to the plasmonic absorption, exhibiting reflection that approaches unity with extremely low loss, through a distinct high‐Q spectral locking of the response of all the constituent plasmonic resonators in the volume; in addition, a transmissive mode that supports the emergence of lattice matched scattered waves within the volume, leading to full transmission through a spectral transparency window. These attractive optical properties of the volume collective modes may lead to a breakthrough in the design of low‐loss and efficient 3D plasmonic metamaterials for novel linear and nonlinear photonic applications. Abstract : Volume collective modes are being studied in 3D plasmonic metamaterials, characterized by a distinct spectral locking of all the plasmonic resonators response. Depending on their excitation conditions, they can exhibit high reflection with extremely low absorption losses, or a full spectral transparency window. This work can lead to a breakthrough in the design of efficient 3D plasmonic metamaterials.